Improved thermoelectric properties of TiNiSn through enhancing strain field fluctuation. (25th September 2017) - Lkhagvasuren, Enkhtaivan; Fu, Chenguang; Fecher, Gerhard H; Auffermann, Gudrun; Kreiner, Guido; Schnelle, Walter; Felser, Claudia
Abstract: M NiSn ( M = Hf, Zr, Ti) -based half Heusler compounds have attracted extensive attention as promising materials in thermoelectric power generation. In this work, the thermoelectric properties of the cheapest composition TiNiSn from this system are investigated. Isoelectronic substitutions of Si and Ge on Sn site are employed to reduce the lattice thermal conductivity. It is found that Si substitution leads to simultaneously enhanced mass and strain field fluctuations in TiNiSn, while the strain field fluctuation dominates the decrease of thermal conductivity in Ge substituted TiNiSn. A maximum ZT of 0.48 at 740 K is obtained in T i N i S n 0.975 G e 0.025, which is a 23% increase compared to TiNiSn. This result highlights the role of strain field fluctuation in suppressing lattice thermal conductivity and improving the thermoelectric performance of half-Heusler compounds.